Induction of immune cytolysis: tumor-cell killing by complement is initiated by covalent complex of monoclonal antibody and stable C3/C5 convertase. - Vogel, C W (1981)
The unique specificity of monoclonal antibodies (Ab) was combined with the cell-killing function of the cytolytic alternative pathway of complement. The functionally C3b-like glycoprotein of cobra venom was linked to a murine monoclonal Ab directed to a human melanoma-associated antigen by a disulfide bond, by using a heterobifunctional crosslinking reagent. The covalent monoclonal Ab-cobra venom factor (CVF) complex exhibited specific cytolytic activity in the presence of normal or C4-deficient serum. It induced killing of melanoma cells but not of LG-2 lymphoblastoid cells or P815 mastocytoma cells. The cytolytic action of the monoclonal Ab-CVF complex was selective in that it was limited to the melanoma cells when these were mixed with one of the two other cell lines. In absence of serum, the complex was noncytotoxic. Monoclonal Ab or CVF alone had no cytolytic activity with or without serum. It is concluded that CVF covalently linked to melanoma cell-bound AB forms the stable C3/C5 convertase with factors B and D of the alternative pathway, which in turn causes formation of the membrane attack complex and thereby cell death.